1B.03: WHITE-COAT AND MASKED HYPERTENSION AS RISK FACTORS FOR PROGRESSION TO SUSTAINED HYPERTENSION. (June 2015) - Sivén, S.; Niiranen, T.; Kantola, I.; Jula, A.
Abstract : Objective: To assess the risk of progression from white-coat hypertension (WCHT) and masked (MHT) to sustained hypertension (SHT) in a nationwide unselected population sample. Design and method: Both office and home blood pressure (BP) were measured in all participants in the years 2000 and 2011. We compared the risk of progression to SHT (office BP >=140/90 mmHg and home BP >=135/85 mmHg or start of treatment with antihypertensive medication) between 528 participants with normotension (NT, office BP <140/90 mmHg and home BP <135/85 mmHg), 142 participants with WCHT (office BP >=140/90 mmHg and home BP <135/85 mmHg), and 63 participants with MHT (office BP <140/90 mmHg and home BP >=135/85 mmHg) with no antihypertensive drug treatment at baseline. Office BP was measured twice by a nurse on a single occasion and home BP was measured twice every morning and evening for one week with a validated, oscillometric device. We used the chi-square and Mantel-Haenszel tests to compare differences and trends in categorical variables. A multivariable-adjusted logistic regression model (adjusted for age, gender, body mass index, diabetes, hypercholesterolemia and smoking) was used to evaluate the association between baseline BP categories and incident SHT. Figure. No caption available. Results: Over an 11-year follow-up, the rate of progression to SHT increased from NT (18%) to WCHT (52%) and MHT (73%), P < 0.0001. Progression to SHT became more likely with an increasing baseline home BP (P for trend <0.0001). During follow-up, 2.4%, 10.4% and 16.4% of participants with NT, WCHT and MHT (P < 0.0001), respectively, suffered a major adverse cardiovascular event (a composite of nonfatal myocardial infarction, nonfatal stroke, hospitalization for heart failure and coronary intervention). The multivariable-adjusted odds ratios (95% confidence interval) for developing SHT, as compared with NT, were 4.6 (3.1–7.0, P < 0.0001) for WCHT and 10.7 (5.7–20.1, P < 0.0001) for MHT (Figure). The other covariates did not reach statistical significance. Conclusions: Neither WCHT, nor MHT can be considered a harmless benign phenomenon. Persons in these categories have a several-fold risk of developing SHT than those with NT and could benefit from active follow-up and lifestyle counselling.